2019
DOI: 10.3389/fphys.2019.00442
|View full text |Cite
|
Sign up to set email alerts
|

Human Physiology During Exposure to the Cave Environment: A Systematic Review With Implications for Aerospace Medicine

Abstract: Background: Successful long-duration missions outside low-Earth orbit will depend on technical and physiological challenges under abnormal environmental conditions. Caves, characterized by absence of light, confinement, three-dimensional human movement and long-duration isolation, are identifiably one of the earliest examples of scientific enquiry into space analogs. However, little is known about the holistic human physiological response during cave exploration or prolonged habitation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The subterranean environment used by H. naledi is not only physically challenging but is also emotionally and physiologically challenging, reflecting an engagement with difficult underground spaces not seen elsewhere in the archaeological record at this time. Dark enclosed spaces, where visual perception is curtailed, can create a state of emotional arousal profoundly affecting perceptual, cognitive and social systems (Zuccarelli et al 2019), even with some form of illumination. While we cannot yet be certain of the exact modes, intensity and quality of the fires used by H. naledi in the Dinaledi subsystem, we can assume that they likely provided flickering and, at best, moderate intensity light sources.…”
Section: H Naledi Buried Their Deadmentioning
confidence: 99%
“…The subterranean environment used by H. naledi is not only physically challenging but is also emotionally and physiologically challenging, reflecting an engagement with difficult underground spaces not seen elsewhere in the archaeological record at this time. Dark enclosed spaces, where visual perception is curtailed, can create a state of emotional arousal profoundly affecting perceptual, cognitive and social systems (Zuccarelli et al 2019), even with some form of illumination. While we cannot yet be certain of the exact modes, intensity and quality of the fires used by H. naledi in the Dinaledi subsystem, we can assume that they likely provided flickering and, at best, moderate intensity light sources.…”
Section: H Naledi Buried Their Deadmentioning
confidence: 99%
“…Kedirgantaraan is a discipline that studies everything related to human exploration efforts in the atmosphere or in outer space [25]. Examples are aerodynamics, structure, aircraft design, materials engineering, human and machine interactions, flight control engineering, aeroelasticity, propulsion engineering, and others.…”
Section: Kedirgantaraan Programmentioning
confidence: 99%
“…Studies from the Antarctic winter showed no significant deterioration in cognitive function 15 16. However, exposure to a dark cave environment was associated with increased reaction time in a systematic review 17. However, participants in both Antarctica and in the cave lived under very restricted and unusual conditions 18.…”
Section: Introductionmentioning
confidence: 99%